Estudo retrospectivo (1998 - 2001) da erliquiose canina em Belo Horizonte: avaliação clínica e laboratorial de infecções experimentais - Simone Magela Moreira (2001)
This paper describes a retrospective study of clinical causística of ehrlichiosis in dogs treated at the Hospital of the Veterinary School, Federal University of Minas Gerais, from March 1998 to September 2001 and the clinical and laboratory evaluation of dogs experimentally infected with Ehrlichia canis Brazilian sample . From the records with confirmation of labiratorial Rhrlichia canis and E. platys were considered demographics (age, race, sex, season and region of origin), clinical parameters (body temperature, presence or history of ticks and clinical signs) and hematological (complete blood cell, and parasitism). 194 chips were analyzed with clinical suspicion of hemoparasitoses, of which 31 animals were infectatos with E. E. canis and 21 with platys. The number of positive diagnosis for ehrlichiosis has increased considerably since 2000, and 24.4% of cases occurred in animals between 13 and 24 months. The most frequent symptoms were fever, anorexia, lethargy, abdominal pain, lymphadenopathy, and dyspnea. With regard to hematological changes, 70.3% of animals had anemia, thrombocytopenia 50% and 30% had leukopenia. The vast majority of infections by E. canis was seen in monocytes. The experimentally infected dogs were monitored during the acute phase of infection by clinical examination, complete blood count, serology rickettsia and research. The prepatent periods ranged from 11 to 13 days, clinical signs were fever, pale mucous membranes, lymphadenopathy, serous nasal secretions and eye-pronounced weight loss. The detection of rickettsia in blood smears proved to be a diagnostic limited, though stages of E. canis were visualized in the bone marrow aspirate material. The results show that, despite the growing clinical cases of canine ehrlichiosis in Belo Horizonte, the diagnostic methods available are still limited and that the lumbar puncture can be used for early detection of E. canis in acute stage of infection